1995
DOI: 10.1007/bf00233450
|View full text |Cite
|
Sign up to set email alerts
|

Expression of potassium channels in epithelial cells depends on calcium-activated cell-cell contacts

Abstract: Harvesting MDCK cells with trypsin-EDTA reduces potassium currents (IK) to a mere 10%, presumably by hydrolysis of K+ channels, but replating at confluence restores them in 12-18 hr, through a process that requires transcription, translation and exocytic fusion of intracellular membrane vesicles to the plasma membrane (Ponce & Cereijido, 1991; Ponce et al., 1991a). In the present work we find that this restoration of IK also requires cell-cell contacts and the presence of 1.8 mM Ca2+. The role of extracellular… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
0

Year Published

1996
1996
2014
2014

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 22 publications
2
8
0
Order By: Relevance
“…S1B, •). Disassembly or assembly of membrane proteins is often reflected by changes in the surface area of the cell, generally owing to altered endo-or exocytosis (18,19). Therefore, we estimated cell surface area through membrane capacitance using impaling glass microelectrodes and observed that 1 μM ouabain decreases this parameter by 26% by the 12th hour, consistent with the fact that ouabain at this concentration causes disassembly and retrieval of cell adhesion molecules (Fig.…”
Section: Resultssupporting
confidence: 70%
“…S1B, •). Disassembly or assembly of membrane proteins is often reflected by changes in the surface area of the cell, generally owing to altered endo-or exocytosis (18,19). Therefore, we estimated cell surface area through membrane capacitance using impaling glass microelectrodes and observed that 1 μM ouabain decreases this parameter by 26% by the 12th hour, consistent with the fact that ouabain at this concentration causes disassembly and retrieval of cell adhesion molecules (Fig.…”
Section: Resultssupporting
confidence: 70%
“…We induced capacitive current transients (IC) (Fig. 1E, above ) with voltage steps from -80 to -90 mV to estimate the membrane capacitance of coupled cells ( see methods ) [26,27] and confirmed that 10 nM ouabain increased the area of the plasma membrane (Fig. 1E, above and below, white vs. red capacitive transients and bars ), reflecting an increase in the number of electrically coupled cells.…”
Section: Resultsmentioning
confidence: 99%
“…GJC was estimated by recording the membrane capacitance of electrically coupled cells using the whole-cell patch-clamp technique [25,26,27]. Patch micropipettes were produced from borosilicate glass tubing (Kimax 51; Kimble) using a puller device (model p-87, Flaming/Brown micropipette puller; Sutter Instruments).…”
Section: Methodsmentioning
confidence: 99%
“…Thus we used it to study the synthesis, assembly, and sealing of tight junctions (TJs) (69,74,75,78,145,183,297), as well as the polarity of Na ϩ -K ϩ -ATPase (61,62,96,102); Enrique Rodriguez-Boulan introduced the use of viruses that bud either apically (e.g., Flu) or basolateraly (e.g., stomatitis) to track the fate of specific proteins during apical or basolateral polarity (283, 284, 379 -382), and Carlos A. Rabito analyzed the onset of polarized cotransporters (368,370,371). M. Taub perfected the approach by developing totally defined culture media (440 -442), and complementary procedures were refined to open and reseal the TJs by removing and restoring Ca 2ϩ (69,97,101,184,186), follow the cascades of phosphorylation involved (20,21,85), the role of the cytoskeleton (311, 312), the participation of protein synthesis and sorting (196,376,379,381), the polarized distribution of ion channels (317,359,360,361,421,439), the involvement of E-cadherin (199 -201), the effect of agents that induce differentiation (280), and the vectorial movement of receptors (302). A distinct advantage of cultured monolayers is derived from the possibility of labeling beforehand a given cell type, and then mixing them with other types from different epithelia and even different animal species (98,…”
Section: Model Systems Of Transporting Epitheliamentioning
confidence: 99%
“…Ca 2ϩ added at this time triggers polarization and junction formation in a few hours, a maneuver called "Ca 2ϩ switch" (184). However, the presence of this ion cannot trigger by itself the development of the transporting epithelial phenotype, as cell-cell contacts are also required (317,411,439). 2؉ …”
Section: E Assembly and Delivery Of The Namentioning
confidence: 99%